Identification of virulent Rhodococcus equi by amplification of gene coding for 15- to 17-kilodalton antigens. - Takai, S (1995)
During a survey of the prevalence of virulent Rhodococcus equi at horse-breeding farms by plasmid and protein profiles, cryptic plasmids of various sizes were found in 66 (3.8%) of 1,725 isolates from feces of horses and 129 (5.9%) of 2,200 isolates from soil. Twenty-two isolates, which contained cryptic plasmids of different sizes, were found by plasmid profiles, and their protein profiles and mouse pathogenicities were examined. Of the 22 isolates, 7 were virulent R. equi, contained both virulence and cryptic plasmids, and expressed 15- to 17-kDa antigens. The remaining 15 isolates were avirulent and did not express the antigens: 6 strains contained cryptic plasmids of two different sizes and 9 strains contained cryptic plasmids of various sizes. A PCR assay was developed for the rapid identification of virulence plasmids of R. equi. Oligonucleotide primers, derived from the sequence of a gene coding for the 15- to 17-kDa virulence-associated antigens of R. equi, amplified a 564-bp product from all the tested isolates harboring a virulence plasmid. This PCR product hybridized with virulence plasmid DNA in the Southern hybridization assay. Virulence plasmid-cured derivatives and all of the tested isolates harboring cryptic plasmids only were negative. The PCR is a rapid, sensitive, and specific test for the identification of virulent R. equi from environmental isolates compared with standard techniques, such as plasmid and protein profiles and the mouse pathogenicity test, and is considered to be a useful tool for epidemiological studies.